Analysis of Vocational School Student’s Mathematical Reasoning in Quadratic Equation - Ronny, Renata Teddy; Putra, Harry Dwi; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
Essay test questions in mathematics learning at Vocational High Schools show that most students have difficulty answering questions about quadratic equations, this is the basis of the research. The reason this problem can occur is because students are not careful in interpreting questions so students cannot master inductive indicators. The purpose of this study is to find out more about students' mistakes when answering questions about mathematics through analysis and description of some of the students' mistakes in answering questions about quadratic equations, therefore this study uses a descriptive method with a qualitative approach. The research subjects were students of class XI Software Engineering at a Vocational High School in Kabupaten Bandung Barat with a total of 15 students. The stages in this research are planning, implementation, and reporting. Student test results as many as three questions are used to collect data. The analysis technique used is data reduction, by presenting the data then conclusions are drawn. The results and discussion of this study showed that students made mistakes in answering quadratic equation questions. The accuracy of students towards questions number 1 and number 3 is still low, so it is necessary to do regular exercises. Students' mathematical reasoning abilities need to be honed again. It can be seen from the results of the answers to question 2 that students have not been able to interpret the questions so that inductive indicators on students' mathematical reasoning abilities have not been fulfilled.